EXPLORING SUSTAINABLE LEADERSHIP: TRENDS AND INSIGHTS FROM A BIBLIOMETRIC ANALYSIS IN BUSINESS AND MANAGEMENT - Ahmad Jusoh; Alhamzah F. Abbas; Hamrila A. Latif (International Journal of Business and Society, 2024)
This study conducts a comprehensive bibliometric analysis of sustainable leadership using 645 documents from the Scopus database, analyzed with VOSviewer software. It examines publication trends, keyword trends, co-citations, co-authorship, and contributions by countries and institutions. The findings highlight the rapid growth of literature in this field, with the United States leading in research output. The analysis shows that sustainable leadership positively impacts organizational performance, including financial outcomes and employee engagement, while cultural factors influence leadership practices across regions. Ethical and transformational leadership are critical in promoting sustainability, especially in supply chain management and innovation within emerging industries. This study identifies key research gaps and offers opportunities for future exploration in sustainable leadership.